Photoshop 7 : - Kabili, Jan (Wiley Publishing, 2003)
Each session explains chapter goals, materials needed, time required, a list of key concepts and features, and additional projects. Each page includes screenshots or photographs to accompany the text. CD-ROM contains all of the files and materials needed for the project